Dampak Faksi dan Konflik dalam Parpol dalam Pemilu Legislatif 2024 - Saiful Fahmi; Siti Fatimah (Bulletin of Community Engagement, 2024)
The party system is one aspect that cannot fail to be reformed. Indonesia has opened its political doors as widely as possible for the establishment of political parties, but the requirements for the establishment and regulation of party organizations are increasingly regulated in the Law (UU). One of the things regulated in party organization is related to efforts to minimize divisions and internal party conflicts, for example, avoiding the occurrence of factions within the body of the political party itself, regarding mechanisms for resolving dual management and mechanisms for organizing party disputes. The formation of factions in internal party conflicts arises due to differences in preferred viewpoints, this can influence Although efforts have been made to strengthen political party cohesion, the problem of internal party conflict has not been resolved rather than resolved, this problem has actually become increasingly common in the recent reform era. This.  This split could have a negative impact on existing parties in Indonesia. The author's aim is to find out what impacts occur within the Party. This research uses descriptive qualitative methods. The research results show that factions leading up to legislative elections often occur resulting in cadres leaving the party and even forming new parties. This is because the general chairman tends to decide on policies that are not absorbed by the cadres below him so that factions emerge within the body of the political party.